If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + 4y = y Solving 15 + 4y = y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 15 + 4y + -1y = y + -1y Combine like terms: 4y + -1y = 3y 15 + 3y = y + -1y Combine like terms: y + -1y = 0 15 + 3y = 0 Add '-15' to each side of the equation. 15 + -15 + 3y = 0 + -15 Combine like terms: 15 + -15 = 0 0 + 3y = 0 + -15 3y = 0 + -15 Combine like terms: 0 + -15 = -15 3y = -15 Divide each side by '3'. y = -5 Simplifying y = -5
| 125-3x=24+23x | | 2x-10i=8-(4y)I | | 27-18=3(X-3) | | 12-8x=123-43x | | -127-8x=-68-10x | | 28+3Y-6=13Y-13-3Y | | 5x+3=27-4x | | 6x+21=5x-51 | | x+19+3x=-15-3x-22 | | 114-6x=9+24 | | 5x+2y-3x+4y= | | 4x+34=5x+1 | | 8x^3-8x^2+x=4x^2-5x+1 | | 3x-7=7x-17 | | 18.23=x+0.21*x | | 7x+13=97-6x | | 75-5x=8x+18 | | 11x-5x+1=-65x+36 | | 3(2x-3)-(4x-5)=0 | | 3x-11=75-5x | | 2x-3=7(x-2)4 | | 3*3-3*3=2 | | 5-5=5X+4X | | 5*9+5*4=280 | | 10W-17W=-49 | | -3-5=-6+X | | 3x(2)+7=5(3x+4) | | 3x+4*5=6 | | 3(x+9)(x-7)=0 | | -4x=17-5 | | A+(n-1)d=45 | | (x^2)+20x=800 |